2013
DOI: 10.1177/1941738113498068
|View full text |Cite
|
Sign up to set email alerts
|

Death After Closed Adolescent Knee Injury and Popliteal Artery Occlusion

Abstract: A healthy adolescent male soccer player sustained a radiograph-negative, effusion-negative physeal injury of the proximal tibia from a ground-level fall with traumatic occlusion of the popliteal artery. Orthopaedic evaluation and arteriography were delayed for 72 hours after the injury. He arrived at a tertiary referral center in multisystem organ failure secondary to lower extremity ischemic necrosis, septic pulmonary thromboembolism, and systemic shock. Emergent medical evaluation, a high index of suspicion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Doppler ultrasonography confirmed the blood flow of crural arteries were intact, which misled us not to perform preoperative CT angiography. The diagnosis of an acute occlusion in popliteal artery after knee dislocation may have more obvious symptoms 3,7,14 . However, chronic occlusion may present solely as a progressive claudication in the extremity 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doppler ultrasonography confirmed the blood flow of crural arteries were intact, which misled us not to perform preoperative CT angiography. The diagnosis of an acute occlusion in popliteal artery after knee dislocation may have more obvious symptoms 3,7,14 . However, chronic occlusion may present solely as a progressive claudication in the extremity 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Popliteal artery injury is associated mainly with high energy injuries such as athletic activities especially in younger population, including knee dislocation and complex fracture of associated bone structures 5,6 . Failure to diagnose may lead to amputation or even death due to systemic inflammatory illness especially in the pediatric population 7,8 . In this report, we present a patient who had a soft tissue defect in lower extremity with ipsilateral popliteal artery occlusion with slow progression due to dislocation of knee in which diagnosis was delayed and led to phalanx amputation and reconstructed with cross-leg free anterolateral thigh flap (ALT).…”
Section: Introductionmentioning
confidence: 99%
“…However, death following popliteal artery injury in blunt trauma is rare [ 9 ]. Reid et al [ 10 ] reported death of an adolescent due to delayed presentation on the third day after blunt knee sports injury with development of systemic inflammatory illness due to popliteal artery occlusion. Lang et al [ 11 ] evaluated concomitant injuries, complications, amputation rates, and outcomes in 64 cases of blunt (54.7%) and penetrating (45.3%) lower limb trauma with popliteal artery injury, along with a death.…”
Section: Discussionmentioning
confidence: 99%
“…Popliteal artery transection injury is a condition resulting in limb necrosis or amputation that can be potentially life-threatening [4]. Severe trauma, including open fracture, gunshot wounds, stabs, knee dislocation and complex fracture of the proximal tibia or distal femur are the principal causes of the high rates of amputation in popliteal artery trauma (Table 1) [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%